The Caspian Sea Environment - Kosarev, Aleksey N.; Kosarev, Aleksey N. (Water Pollution,, 2005)
The systematic description of the knowledge accumulated on the physical oceanography, marine chemistry and pollution, and marine biology of the Caspian Sea forms the basics of this book. It presents the principal characteristic features of the environmental conditions of the sea and their changes in the second half of the 20th century. At present, the principal problems of the Caspian Sea are related to the interannual sea level changes and their forecast and to the estimation of the intensity of the chemical pollution of the sea and its impact upon the biota. Special attention is paid to socio-economic, legal, and political issues in the Caspian Sea region. This publication is based on numerous observational data collected by the authors of the chapters during sea expeditions, on the archive data of several Russian oceanographic institutions, as well as on the broad scientific literature mainly published in Russian editions. This book is addressed to the specialists concerned in research in various fields of physical oceanography, marine chemistry, pollution studies, and biology; solving a wide scope of problems from the regional climate to the mesoscale processes; and using a variety of methods from remote sensing of the seas to numerical and laboratory modeling.